Antecedents of Electronic Word-of-Mouth (e-WOM) and Purchase Intention: The Moderating Role of Consumer Involvement - Miranti Setiawardani; Afrima Widanti (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This research aims to investigate the antecedents of electronic word-of-mouth (e-WOM), specifically source credibility and information accuracy, as well as the influence of e-WOM on purchase intention. Additionally, the study examines the role of consumer involvement as a moderating variable between e-WOM and purchase intention among Shopee e-commerce users.Method: The research employs a quantitative method, collecting primary data through a questionnaire distributed via social media platforms across Indonesia. The participants included 214 Shopee users interested in beauty products serving as the unit of analysis. The data were analyzed using Structural Equation Modeling (SEM) with AMOS version 23.Result: The findings indicate that source credibility positively and significantly impacts e-WOM, establishing it as an antecedent factor. In contrast, information accuracy does not significantly affect e-WOM, suggesting it is not an antecedent factor. Furthermore, e-WOM positively and significantly influences purchase intention. While consumer involvement affects purchase intention, it does not directly moderate the relationship between e-WOM and purchase intention.Practical Implications for Economic Growth and Development: This study offers strategic insights for e-commerce companies to enhance their quality and underscores the importance of credibility and reviews in marketing to boost product sales. Consequently, it presents a novel strategy within the digital marketing landscape that supports economic growth.